Analisis Perhitungan Harga Pokok Produksi Menggunakan Metode Full Costing pada UMKM Warung Nasi Hotha: Analysis of the Calculation of Cost of Production Using the Full Costing Method in MSMEs Warung Nasi Hotha - Dandi Dwiki Ahmad Pratama; Zenith Shalahan Muhammad; Achmad Habibie; Christopher Febrino Pakpahan; Ajis Hidayatullah (Jurnal Manajemen dan Akuntansi Cakrawarti, 2026)
The culinary MSME sector in West Jakarta faces significant challenges regarding cost management accuracy, particularly in determining the cost of goods manufactured. Warung Nasi Hotha, the subject of this study, currently relies on traditional cost recording that overlooks indirect expenditure elements. This research aims to identify all production cost components, calculate the Cost of Goods Manufactured (COGM) using the full costing method, and analyze the discrepancy between the business's internal calculations and standardized cost accounting. The research employs a quantitative descriptive method, with data collected through in-depth interviews, direct observation, and documentation of simple financial reports. The analysis focuses on three menu categories: normal portion, additional chicken, and additional fish. The results indicate that COGM under the full costing method is consistently higher than internal business calculations, as it incorporates both fixed and variable overhead costs such as utilities, rent, and transportation. Significant COGM gap per portion were fauna for each menu, indicating a clear distortion in cost information. The implication of these findings highlights the necessity for MSME owners to implement comprehensive cost accounting to avoid "pseudo-profits" and ensure long-term business sustainability amidst competitive market dynamics.